2019
DOI: 10.1177/1049732319869908
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dialysis on the Dyadic Relationship Between Male Patients and Their Female Partners

Abstract: The objective of this study was to explore the impact of three early phases of renal dialysis, namely pre-dialysis, starting dialysis, and establishing dialysis, on dyadic relationships. Twenty UK-based dyads (20 male patients and their female partners) participated in semi-structured interviews and discussed the effects of dialysis on themselves and their relationship. Dyadic thematic analysis, facilitated by dyadic-level charting, integrated participants’ experiences and enabled identification of patterns ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…The data used in this phase of the study were part of an over-arching, cross-sectional, qualitative study which explored the impact of the early phases of dialysis on patients and their partners [ 3 ]. The early phases of dialysis were defined as the period when patients are preparing to start dialysis (e.g., pre-dialysis) and are adjusting to dialysis [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The data used in this phase of the study were part of an over-arching, cross-sectional, qualitative study which explored the impact of the early phases of dialysis on patients and their partners [ 3 ]. The early phases of dialysis were defined as the period when patients are preparing to start dialysis (e.g., pre-dialysis) and are adjusting to dialysis [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous qualitative research found that psychological and interpersonal factors within the dyad played an important role in adjusting to dialysis and minimising the impact of it on the dyadic relationship and quality of life (QOL) [ 3 ]. Moore et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations